HAKIKAT KEBENARAN ILMIAH DALAM TRADISI FILSAFAT BARAT DAN ISLAM: STUDI LITERATURE REVIEW KONSEP ONTOLOGI EPISTEMOLOGI - Ega Pangalingan; Andi Ridwan; Ardiansyah Setiawan; Muh. Dzakwan Mangawiang; Fadli; Zulkifli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the nature of scientific truth in Western and Islamic philosophical traditions through a comparative analysis of ontological and epistemological concepts. The problem stems from the gap in understanding the philosophical foundations of scientific truth that differ diametrically between the two traditions, where the West has separated the domains of religion and science since the Renaissance era, while Islam maintains a holistic view that integrates revelation, reason, and experience. The research method employs a qualitative approach with systematic literature study analyzing relevant primary and secondary sources from classical to contemporary periods. The research findings indicate that ontologically, the West constructs reality based on secular materialism while Islam is based on the holistic principle of tawhid. Epistemologically, the West relies on rationalism and empiricism, whereas Islam positions revelation as the primary source complemented by reason. Despite fundamental differences, both traditions share the same commitment to the pursuit of truth. This research contributes to the development of comparative epistemology and offers a methodological framework for cross-traditional researchers in designing research sensitive to differences in philosophical assumptions.